2005
DOI: 10.1073/pnas.0503742102
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for ordered substrate binding and cooperativity in aspartate transcarbamoylase

Abstract: X-ray structures of aspartate transcarbamoylase in the absence and presence of the first substrate carbamoyl phosphate are reported. These two structures in conjunction with in silico docking experiments provide snapshots of critical events in the function of the enzyme. The ordered substrate binding, observed experimentally, can now be structurally explained by a conformational change induced upon the binding of carbamoyl phosphate. This induced fit dramatically alters the electrostatics of the active site, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 40 publications
3
86
0
Order By: Relevance
“…Indeed, according to the linkage equations of Wyman (35,36), it follows that aspartate and its analogs have higher affinity for the T state than for the R state of ATCase, a result difficult to reconcile with the fact that the wild-type enzyme exhibits cooperative aspartate binding. In a recently reported in silico docking study, CP and aspartate were found to bind in strongly overlapping positions within the active site of the unliganded wild-type enzyme (13). Only in the presence of CP does aspartate bind productively.…”
Section: Direct Evidence Of a Thermodynamic Equilibrium Between Diffementioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, according to the linkage equations of Wyman (35,36), it follows that aspartate and its analogs have higher affinity for the T state than for the R state of ATCase, a result difficult to reconcile with the fact that the wild-type enzyme exhibits cooperative aspartate binding. In a recently reported in silico docking study, CP and aspartate were found to bind in strongly overlapping positions within the active site of the unliganded wild-type enzyme (13). Only in the presence of CP does aspartate bind productively.…”
Section: Direct Evidence Of a Thermodynamic Equilibrium Between Diffementioning
confidence: 90%
“…Two functional and structural states of the enzyme have been characterized by a variety of techniques: a less active, low-affinity, T-state, stabilized by CTP and a more active, high-affinity, R-state stabilized by the substrates or the bisubstrate analog Nphosphonacetyl-L-aspartate (PALA). The corresponding crystal structures (11,12) recently refined (13,14) described the T-to-R transition as an 11-Å (1 Å ϭ 0.1 nm) expansion along the 3-fold axis together with subunit and domain rotations (15) resulting in disruption of the r1-c4 interface between regulatory and catalytic chains. This quaternary rearrangement is accompanied by tertiary changes in both the catalytic and regulatory chains, most notably the 80s and 240s loops of the catalytic chains.…”
mentioning
confidence: 99%
“…15 The molecular mechanism responsible for the ordered binding of Asp, which takes place only after CP binds in the active site has been proposed based upon structures of ATCase in the absence and presence of CP. 13 The binding of CP induces local conformational changes resulting in the formation of a new highly electropositive binding pocket for Asp. 13 To understand the binding of Asp to the enzyme•CP complex and the concurrent conformational changes induced by Asp binding, X-ray crystallography was employed.…”
Section: Resultsmentioning
confidence: 99%
“…13 The binding of CP induces local conformational changes resulting in the formation of a new highly electropositive binding pocket for Asp. 13 To understand the binding of Asp to the enzyme•CP complex and the concurrent conformational changes induced by Asp binding, X-ray crystallography was employed. We were able to obtain data quality crystals of the R state of the enzyme with substrates bound by utilized a mutant version of the enzyme with the D236A mutation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation